Persepsi Pelaku Usaha Rumah Makan Warga Muhammadiyah Kota Medan Terhadap Kewajiban Sertifikasi Halal - Khairil Azmi Nasution; Dianto Dianto; Muhammad Irsyad (Iuris Studia: Jurnal Kajian Hukum, 2023)
Perception is an individual's response to something that can be influenced by knowledge. Good individual knowledge about the obligation of Halal certificate for food business actors will affect their perception of the obligation of Halal Certification for restaurant business actors. The knowledge of restaurant businesses owned by Muhammadiyah residents regarding Law No. 33 of 2014 concerning Halal Product Guarantees, Law No. 11 of 2020 concerning Job Creation and Government Regulation No. 39 of 2021 concerning Implementation of Halal Product Guarantees is quite high, including awareness of consuming halal law. mandatory according to religious orders, thus affecting their perception of the Halal Certificate Obligation. However, at present, there are no Muhammadiyah residents who have a restaurant business who have a halal certificate. This study aims to determine the level of understanding of the obligation of halal certificates on the food of restaurant owners in the Muhammadiyah community in the city of Medan. The data in this panel were collected by conducting interviews and observations of the owners of restaurants owned by Muhammadiyah residents in the city of Medan. Then, analyzed using product moment correlation and qualitative descriptive. The informants who were interviewed in the study were the owners of the Muhammadiyah Restaurant Residents who were domiciled in Medan City.